Reaction Mechanisms of Methane for Modelling Combustion and Suppression - Zeng, W.R.; Chow, W.K. (Asian Journal of Chemistry, 2010)
A recent study on combustion chemistry of methane is reported in this paper. Detailed combustion mechanisms have been described by identifying the key intermediate reactions. Some reduction mechanisms under different conditions are also discussed. The inhibiting effect of some fire-suppressing agents on the combustion of methane and the oxidation mechanisms of methane in supercritical water are introduced. The calculation of heat of combustion indicates that the value of 13.1 MJ/kg of oxygen consumed is applicable for estimating the heat release of burning methane in air.